Numerical Simulation of the Thermal-Hydro-Mechanical Characteristics of High-Speed Railway Roadbeds in Seasonally Frozen Regions - Yuzhi Zhang; Jianghui Bei; Pei Li; Xiaojie Liang (Advances in Civil Engineering)
A multiphysics mathematical model of high-speed railway (HSR) roadbeds is necessary to facilitate a good level of understanding of the frost heaving mechanism. Based on the classical hydrodynamic model and fundamental thermoelasticity theories, we propose a thermo-hydro coupled model, based on the soil-water characteristic curve and solid-liquid ratio as the relation equations, with the effects of the ice-water phase change and water migration due to temperature change considered. With the linear expansion coefficient related to the temperature and the mass of ice content in roadbeds as the relation equation, we establish a macroscopic thermal-hydro-mechanical model for unsaturated soil to calculate the roadbed deformations. Based upon the field data of a typical cross section of the Harbin-Dalian HSR roadbed, the variation of the thermal-hydro-mechanical characteristics is simulated and studied. The results demonstrate that the increase of water content in the roadbed’s central line mainly appears in soil layers at depths less than 1.2 m and most ice-containing soil layers are at depths less than 0.6 m. Under the driving force of thermal and hydraulic migration, the vertical displacement of the west shoulder is increased to 18 mm. Then the settled maximum surface unevenness reaches 16 mm between the shoulder and centre line.